Denotate of the Scientific and Psychological Term "Game" - Moskalets, Victor (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The essential psychological properties of any activity lie in its motivation in particular in those purposes that lead the subject to it as a means of achieving them. Various positively colored emotional experiences awaken in the subject in the process of playing (games), such as the joy of excitement, elation, and so on create a basis of its motivation. Acquisition and use of material goods and / or social benefits have never been the motives of a game as such; it does not belong to the future or the past, but only to the present moment - to its own course here and now. However, such a motivational basis is inherent not only to a game, but also to some other activities. The so-called game tools, used by other activities, are clearly divided into two types: 1) educational and developmental (training, business, role, etc.); 2) psychotherapeutic. The subject seeking to use these tools effectively should be dominated by motivation matching their purpose. Thus, the former "belong to the future" in the sense that their basis is purpose, not some game result, but developmental, correctional and therapeutic result etc.; and the latter belong to the past, as they are to help their participants to get rid of the past pathologies effects. Therefore, according to the criterion of motivation, these "game" tools are not actually games. Differntia specific of playing/game is the creation of purely imaginary playing situations. It is this property that is the predicate-discursive basis of the term "game" denotation. The rest of its meanings are connotations and other similarities and associations, in particular superficial ones that create definitive relativism in the semantic field of playing/game theory. Among the necessary conditions and essential components of games/fictional playing situations, "fakes", pretense, etc., there are rules that ensure the functioning of a game; deviations and rule-breaking spoil and devalue the game. The subject accepts the restrictions on his freedom by the rules of the game willingly and follows them gladly, because restrictions of the game are conditions created to achieve "courage", and the subject tests their mental and physical abilities (intelligence, agility) etc. and proves them to themselves and others. This means that in the process of the game the vital forces, energies, resources of the subject "play", and they are the source of admiration, comfort, and pride, especially if the game impresses important to them individuals and groups of people with skills, beauty, and delight. Thus, the game (playing) is the creation of purely imaginary playing situations with mandatory rules of conduct, where players can test and demonstrate their mental and / or physical abilities, inclinations, strengths, and which provides enthusiasm, inspiration, strength, joy, pleasure, etc. (it allow to " play " their vital forces), and therefore participants willingly play those games that bring them such experiences.